A Critical Discourse Analysis of Euphemisms and Dysphemisms in News Reports on Sexual Violence on Tirto.id - Ida Ayu Alit Srilaksmi; Dewi Yuri Cahyani; Ade Devia Pradipta (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
In communication practices, language is a fundamental aspect that plays a crucial role as a medium for exchanging information, developing personal identity, and sharing experiences among individuals. Language holds a central role in shaping public perception of social realities, including in mass media reporting on sexual violence cases. This study aims to critically analyze the use of euphemistic and dysphemistic language styles in news coverage of sexual violence published by the online media outlet Tirto.id. This is a qualitative study using a postmodern feminist perspective and Sara Mills’ model of critical discourse analysis. The research data consist of five news articles published by Tirto.id during July 2024, focusing on sexual violence cases, as well as direct information obtained from the Tirto.id media production team. Data collection techniques include textual analysis and thematic analysis. The results show that out of the five analyzed articles, there were 16 instances of euphemistic language and 17 instances of dysphemistic language. In addition to textual analysis, this study also applies a multilayered approach by examining the factors influencing text production and the sociocultural contexts behind the news production process based on hierarchy of influnces theory. The study concludes that the choice of language style in media reporting is not merely a linguistic decision, but also carries ideological weight, influencing how society understands and responds to the issue of sexual violence. Therefore, it is crucial for the media to adopt a critical and ethical stance when selecting the diction used in news coverage.